Prevalence and its associated factors of diabetic retinopathy among type 1 and type 2 diabetic patients at public hospitals in Eastern Ethiopia, 2023: a hospital-based comparative cross-sectional study - Bayisa, Feyisa Shasho; Demis Nimani, Teshome; Darcho, Samuel Demissie (Frontiers in Clinical Diabetes and Healthcare, 2024)
IntroductionDiabetic retinopathy (DR) is a highly prevalent microvascular disease among diabetic patients, resulting in irreversible blindness. However, there is a dearth of evidence on diabetic retinopathy (DR) and its associated factors in eastern Ethiopia. The study aimed to determine the prevalence of diabetic retinopathy (DR) and its associated factors among type 1 and type 2 diabetic patients at public hospitals in eastern Ethiopia.MethodA hospital-based comparative cross-sectional was conducted among 520 diabetic patients. Epidata software was used for data entry, and STATA version 17 was used for statistical analysis. Multivariate binary logistic regression was computed to identify factors associated with DR. The Hosmer and Lemeshow chi-square test assessed goodness of fit.ResultsThe overall prevalence of DR was 43.5%. The prevalence of diabetic retinopathy among type 1 DM was 38.5%, and the prevalence of DR among type 2 DM was 48.5%. Age >60 [AOR = 4.64 95% CI (1.60, 13.51)], being male [AOR = 4.05 95% CI (1.51, 10.97)], and having complications [AOR = 0.01 95% CI (0.003, 0.04)] were significantly associated with DR among type 1 diabetes. Having a family history of DM [AOR = 1.57 95% CI (1.76, 3.24)], poor glycemic status [AOR = 1.91 95% CI (1.56, 2.83)], and having complications [AOR = 11.07 95% CI (4.89, 25.13)] were significantly associated with DR among type 2 diabetes.ConclusionsIn the current study, the prevalence of DR was 43.5%. The prevalence was higher among type 2 diabetes compared to type 1 diabetes. Factors such as poor glycemic control, older age, male sex, a family history of diabetes, and complications related to diabetes were significantly associated with DR. To minimize the impact of diabetics, it requires regular screening programs for diabetic patients, especially those with poor glycemic control and other identified risk factors.